Non-Observance Of Grice's Maxims Found In The Death Of ASalesman Drama Script By Arthur Miller: A Pragmatic Study - Triyatun, Triyatun; , Agus Wijayanto, MA. P.hD; , Dra. Siti Zuhriah Ariatmi, M.Hum (2013)
This research is aimed at describing the types of non-observance maxims, and the intentions of non-observance maxims. The type of this research was descriptive qualitative research which the researcher used documentation method as the method of collecting data. The data of this research were dialogues which contain non-observance maxims that were found in The Death of Salesman drama script. The result of this research showed that firstly, the types of non-observance in The Death of a Salesman drama script used by the characters were flouting of maxims, violating of maxims and suspending of maxims. Secondly, the speaker's intentions of nonobservance maxims were requesting, suggesting, alerting, warning, refusing, and disagreement utterance.